Citizens' perceptions of standards in public life - Rose, Jonathan (2012)
This thesis analyses citizens' perceptions of standards in public life. It attempts to understand whether perceptions such as these are important substantively for questions of citizen disaffection, and begins the task of analyzing how citizens come to hold the perceptions they do. The thesis presents a systematic investigation into this topic, placing perceived standards in the context of a discussion about citizen disaffection and the perceived legitimacy of political systems. As they are conceived of in this thesis, 'standards in public life' can usefully be thought of as the 'rules of the game' or the 'spirit of public service'. Standards in public life are less a set of formal, prescriptive rules, more an exhortation to the appropriate exercise of public office. Such a focus upon the 'rules of the game' results in the primary concern of this thesis being about the process of governing, as opposed to the outcomes governors can produce.